2020
DOI: 10.1093/ehjacc/zuaa016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk scores identify more patients at risk for cardiovascular events within 30 days as compared to standard ACS risk criteria: the WESTCOR study

Abstract: Aims Troponin-based algorithms are made to identify myocardial infarctions (MIs) but adding either standard acute coronary syndrome (ACS) risk criteria or a clinical risk score may identify more patients eligible for early discharge and patients in need of urgent revascularization. Methods and results Post-hoc analysis of the WESTCOR study including 932 patients (mean 63 years, 61% male) with suspected NSTE-ACS. Serum samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…We tried to communicate with the corresponding authors of the abstracts via email for their published studies in full text, but received only studies that were already included. Therefore, 10 studies were finally included and considered eligible for systematic review and analysis [9,10,33–40] (Supplementary Figure 1, Supplemental digital content 2, http://links.lww.com/EJEM/A332 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tried to communicate with the corresponding authors of the abstracts via email for their published studies in full text, but received only studies that were already included. Therefore, 10 studies were finally included and considered eligible for systematic review and analysis [9,10,33–40] (Supplementary Figure 1, Supplemental digital content 2, http://links.lww.com/EJEM/A332 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review, 33 843 patients were included from 10 studies [9,10,33–40]. Five studies were conducted in Europe [9,33,34,38,40], one in Asia [37], and the rest in North America [10,35,36,39]. Seven studies were conducted in the EDs [9,10,34–38] and three studies were in the prehospital [33,39,40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T-MACS has been externally validated in 1,459 patients from three prospective studies in the United Kingdom [5], 1,244 patients from Australasia [6], and multicentre prospective trials from the United Kingdom [7], Thailand [8] and Norway [9], each of which demonstrated acceptable predictive performance. A pilot randomized controlled trial of a precursor version of the algorithm showed that its use led to significantly more safe discharges from the ED within 4 hours of arrival than standard care [10].…”
Section: Introductionmentioning
confidence: 99%